2017
DOI: 10.1145/3140659.3080211
|View full text |Cite
|
Sign up to set email alerts
|

Hardware Translation Coherence for Virtualized Systems

Abstract: To improve system performance, modern operating systems (OSes) often undertake activities that require modification of virtual-to-physical page translation mappings. For example, the OS may migrate data between physical frames to defragment memory and enable superpages. The OS may migrate pages of data between heterogeneous memory devices. We refer to all such activities as page remappings. Unfortunately, page remappings are expensive. We show that translation coherence is a major culprit and that systems empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 63 publications
2
17
0
Order By: Relevance
“…As a result, in addition to the list of victim vCPUs approximated by the guest OS, the list of victim cores is approximated by the VMM. Combined with the flushing of translation structures upon a nested page table update, these approximations result in frequent needless evictions of unrelated translations [44]. TLB shootdown activity has been observed to be a significant bottleneck in prior studies [4,6,12,25,33,40,44] and is also confirmed by our own experiments.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…As a result, in addition to the list of victim vCPUs approximated by the guest OS, the list of victim cores is approximated by the VMM. Combined with the flushing of translation structures upon a nested page table update, these approximations result in frequent needless evictions of unrelated translations [44]. TLB shootdown activity has been observed to be a significant bottleneck in prior studies [4,6,12,25,33,40,44] and is also confirmed by our own experiments.…”
Section: Introductionsupporting
confidence: 83%
“…Current VMMs do not track the gVA of pages used by the guest. Since modern processors only permit invalidations of individual TLB entries when the gVA (for guest pages) is known, when the VMM updates the nested page table, translation structures are completely flushed [44]. Repopulating the flushed 2-dimensional page tables are very expensive.…”
Section: Introductionmentioning
confidence: 99%
“…Hardware-based TLB shootdown. There have been a number of approaches to handle the problem of TLB cache coherence at the hardware layer [7,10,12,42,43,48,49,51,60,62]. Several of these hardware-based approaches attempt to squeeze performance using non-traditional TLB designs, such as multi-level TLB hierarchies.…”
Section: Related Workmentioning
confidence: 99%
“…Furthermore, UNITD adds a costly content-addressable memory (CAM) to each TLB to perform reverse address translations when checking whether a page translation is present in a specific TLB, thereby greatly increasing the TLB's power consumption. HATRIC [62] is a hardware mechanism similar to UNITD and piggybacks translation coherence information using the existing cache coherence protocols.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation